The Role of the Prosecutor's Office in Resolving Criminal Corruption Cases - Prakoso, Aji Satrio; Richard, Richard (Devotion : Journal of Research and Community Service, 2024)
The Prosecutor's Office plays a crucial role in the functioning of the legal system. However, in reality, the Corruption Court is still located in every provincial capital in Indonesia, which often results in high costs for resolving corruption cases which are sometimes disproportionate to the losses they cause to the state. The author of this research focuses on analyzing circular letters belonging to the Deputy Attorney General for Special Crimes by linking the theory of Legal Economic Analysis as a form of consideration and also explaining how the Prosecutional Office applies a restorative justice approach. The research contributes to the topic discussed by evaluating the policy's significance and the prosecutor-office's role in handling corruption cases through the application of restorive justice principles. This study also aims to provide an overview of the challenges and technical legal issues faced by the public prosecutor in carrying out their responsibility to recover funds and/or state assets.